Effect of replacing whole wheat with broken rye as a sustainable grain in diets of fattening turkeys on growth performance, litter quality, and foot pad health - Lingens, Jan Berend; Visscher, Christian; Sürie, Christian; Grone, Richard; von Felde, Andreas; Wilke, Volker; Abd El-Wahab, Amr (Frontiers in Veterinary Science, 2023)
Rye is one of the most important cereal crops in Central Europe, thus attempts have been made to include it in the diets of birds to reduce production costs, since the cost of feed accounts for as much as 50 %–70 % thereof. Nevertheless, the use of rye has been limited to date, particularly in turkeys. This study aimed to test the effects of rye inclusion up to 10 % on growth, excreta, and/or litter dry matter (DM), and foot pad health. Four trials were performed with a total of 4322, 4307, 4256, and 4280 female turkeys (BUT BIG 6, Aviagen) for trials 1, 2, 3, and 4, respectively. All birds were fed commercial starter diets for the dietary phases 1 and 2 (up to d 35 of life). Thereafter, at the start of the study, the control group received commercial diets until the end of the fattening period. A supplementary feed was offered to the experimental group to which increasing levels of rye were added (stepwise from 5 % and 10 %). Using supplementary feed with rye showed no significant differences in the final body weight between the control and experimental groups (10.9 kg vs 10.8 kg). The DM content of fresh excreta for turkeys during the experimental period did not show significant differences between both groups, except at weeks 10 and 14 of life. The feed type (either commercial diet or experimental diet with broken rye) did not significantly affect litter DM content between the groups throughout the experimental period. No significant differences were noted in food pad dermatitis (FPD) scoring between both groups throughout the experimental period, except at weeks 11 and 16 of life. Overall, this study showed that including proportions of rye up to 10% could replace conventional ingredients and may increase sustainability in poultry production regardless of the addition of supplementary feeds.